The effect of silent short movie on EFL writing achievement of Vocational High School students - Rahmani Ayu Rinda Kartika; S. Susilo; Muhammad Natsir (Jurnal Pendidikan Vokasi, 2017)
The purpose of the study was to investigate whether or not there is a significant effect of silent short movie on EFL writing achievement of the vocational high school students. This study was quasi-experimental using a nonrandomized control group, pretest-posttest design. There were 61 students who were selected randomly from the 10 classes of tenth-graders of the 6th State Vocational School in Samarinda. The instruments used in the study was writing test. The result revealed that the vocational high school tenth grade students who were taught by silent short movie (M = 8.01, SD = .32) got significantly different achievement in EFL writing than did the vocational high school tenth grade students who were not taught by silent short, t(58) = -2.22, p = .030. This result suggests that the writing aspects which the students significantly outperformed were text organization, sentence formation, grammar, vocabulary, mechanics, and tidiness.